Histological Evaluation of Local Estrogen Administration on the Healing of Traumatic Alveolar Bone Defect in Rabbits (Experimental Study) - Asmaa S Aldouri; Abdalsatar S Almaadhidi; Israa A Abdalhameed (University of Mosul, College of Dentistry, 2013)
Aims:This study carried out for histological assessment of the effect of local administration of estrogen hormone after mixing with collagen fiber of bovine bone on healing oftraumatic alveolar bone defect in the rabbits.Materials and Methods:Eight Rabbits were used, the vertical fissure was done in the man-dibular alveolar bone of the control group was filled with natural collagen fiber of bovinebone, while in the experimental group , this fissure was filled with estrogen hormone mixed with natural collagen fi-ber of bovine bone.Histological studies and statistical analysis were done.Results:The results showed that local administrations of estrogen hormone enhance new bone formation and new vascularization which is statistically significant when compare with control group.Conclusions: This study illustrate that the estrogen has an osteoinductive action to enhance bone healing process. Biostatistical analysis was shown significant relation; so bone healing enhanced by this material.